Research on Fair Trade Consumption—A Review - Andorfer, Veronika A.; Liebe, Ulf (2012)
An overview and assessment of the current state of research on individual consumption of Fair Trade (FT) products is given on the basis of 51 journal publications. Arranging this field of ethical consumption research according to key research objectives, theoretical approaches, methods, and study population, the review suggests that most studies apply social psychological approaches focusing mainly on consumer attitudes. Fewer studies draw on economic approaches focusing on consumers’ willingness to pay ethical premia for FT products or sociological approaches relying on the concept of consumer identity. Experimental, qualitative and conventional survey methods are used approximately equally often. Almost all studies draw on convenience or purposive samples and most studies are conducted in the USA or the United Kingdom. Several problems in current research are identified: amongst others, studies’ rather narrow theoretical focus, potential hypothetical and social desirability bias of conventional survey data, and a lack of generalizability of empirical findings. In turn, we suggest that research would benefit from both a multiple-motives and a multiple-methods perspective. Considering competing theories can help to single out key behavioral determinants of individual FT consumption. The combination of different methods such as conventional surveys and field experiments contributes to uncovering respondents’ truthful answers and improves generalizability of results. Scholars in the field of ethical consumption research should use experiments to detect causal relations proposed by theories and conduct cross-country surveys to gather insights as to how differences in market structures, cultural traits, and other path dependencies affect patterns of individual FT consumption.
Keywords: theory of planned behavior; Fair Trade consumption; Field Experiment; Ethical consumption; Choice experiment